Analysis on the factors and effects of engine tapping noise by Design of Experiment (DOE) / Mohd Shahrudin Mohd Alias … [et al.] - Mohd Alias, Mohd Shahrudin; Saad, Nor Hayati; Saedon, Juri; Hassan, Nor Hidayahti; Harun, Saidi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
The effect of various factors on engine noises have been studied in several ways involving component simulation and product investigations. However, the solution remain exclusive and investigation may be expensive but yet to solve the engine noise issues entirely for several engine Original Equipment Manufacturers (OEMs). Manufacturing has many factors that much to be considered and this includes the uncontrolled or 'noise 'factors that exist within the process and product operation. The main research objective is to determine the optimum combination of control factors for engine valvetrain tapping sound while robust to noise factors by using Taguchi method. The objective is also to identify the most significant factors by using Analysis of Variance (ANOVA) approach. In this study, the effects of seven controlled factors and two uncontrolled factors were investigated by implementing the Orthogonal Arrays (OA) of Taguchi experimental method on a DOHC gasoline engine. The Orthogonal Array design of L₈2⁷ was chosen and eight experiment runs with pre-test run were conducted at the manufacturing plant in actual engine running condition. The optimum parameters from the DOE yield the best sound pressure level of 70.34 dB SPL based on software prediction, while the most significant factor found to be considered for improvement was the camshaft exhaust waviness of minimum level (waviness curve-maximum, WCM 2.0jum and below). Based on the confirmation run result, the optimum parameters yield the actual sound pressure level of 70.4 dB SPL which equal to predicted value. This result further convince that the implemented methodology is effective to find the best combinations of the studied factor parameters and able to reduce the engine valvetrain noise level.